On the indentation-assisted phase engineered Si for solar applications. (15th July 2020) - Mannepalli, Sowjanya; Sagade, Abhay A.; Mangalampalli, Kiran S.R.N.
Abstract: The rhombohedral phase of silicon is fabricated over a large-area within the diamond cubic Si wafer using spherical nanoindentation. The ultraviolet and visible spectrum showed a 50% lower reflectance for the rhombohedral Si compared to the pristine Si. The estimated refractive index of 6.7 at 630 nm for the rhombohedral Si is 35% higher than the diamond cubic Si, which agrees well with the theoretical calculations. The rhombohedral Si with enhanced light absorption ability is utilized as a solar absorber layer for the bare p-n junction Si solar cell and observed to show 10 times improvement in the photocurrent density. Graphical abstract: Image, graphical abstract